Connections between RNA Polymerase II transcriptional regulation, nucleosome arrangement and DNA damage - Foxwell, J (2017)
Transcription by RNA polymerase II (RNAPII) is a central process in gene expression and so subject to many layers of regulation: post-translational modifications of the RNAPII C-terminal domain (CTD), transcription factor association, chromatin compaction and the control of polymerase access to DNA. Transcription can also be altered when DNA damage is encountered. My thesis addressed different aspects of these regulatory mechanisms. Firstly I studied the role of RNA:DNA hybrids (R-loops) in pause-type termination, and assessed whether data based on the β-actin gene could be extended to further genes. I also investigated whether DNA damage repair (DDR) factor Rad51 is present over R-loop associated pause regions. Secondly I studied the roles of tyrosine and threonine phosphorylation (Y1P and T4P) of the RNAPII CTD, by testing their association with DDR and transcription termination respectively. I also developed a modified MNase-seq protocol using mNET-seq isolation conditions to allow close comparison between chromatin configuration and the nascent RNA signal. The outcome of my research was that I found the PKM gene exhibits the same basic characteristics of pause-type termination, including R-loop formation. However, little evidence for heterochromatin formation as observed for β-actin termination was identified. I also showed that Rad51 accumulates at R-loop regions in pause-type termination, but does not appear to induce R-loops. More likely Rad51 is recruited by downstream DDR factors. Y1P is associated with factors involved in UV DDR. My studies showed that UV damage causes a global RNAPII elongation defect with altered chromatin associated histone marks and defective recruitment of elongation factors including the PAF1 complex and SPT6 to the polymerase. Finally my studies on T4P-associated termination cis-elements indicated that positions of cleavage-independent termination are formed relative to mRNA 3’ ends but not based on specific DNA sequence. Also cleavage factor depletion increased mononucleosome signals in these termination regions.